COMPARATIVE ANALYSIS OF RESERVOIR PROPERTIES OF CONSOLIDATED TERRIGENOUS ROCKS OF DNIEPER-DONETSK DEPRESSION OF THE EASTERN SLOPE OF THE LVIV PALEOZOIC DEPRESSION - VYZHVA, Serhii; ONYSHCHUK, Viktor; ONYSHCHUK, Dmytro; ONYSHCHUK, Ivan; SHABATURA, Oleksandr (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. The paper concerned the results of comparative analysis of the reservoir properties of consolidated terrigenous Carboniferous rocks of the northern and central graben of the Dnieper-Donetsk depression and the Cambrian of the Lviv Paleozoic downfold of promising hydrocarbons areas. The purpose of the research was to study and compare the petrophysical parameters of consolidated reservoir rocks of the studied areas as the basis of a comprehensive analysis of their physical properties.Methods. Determination of dry-bulk density of samples by their weighing and measuring their geometric dimensions. The method of hydrostatic weighing of the samples (saturated by model of the reservoir water) was used. Digital analytical scales (accuracy +_0,001 g) were used to determine the weight of samples. The open porosity factor was determined by the gas volumetric method and by the method of hydrostatic weighing according to the standard method. Capillametric studies were performed by centrifugation of samples. To establish correlation between the capacitive, electrical and acoustic parameters of rocks in atmospheric and reservoir conditions, a complex of petrophysical studies with physical modeling of formation conditions was performed.Results. Such reservoir parameters as the open porosity factor and void factor, permeability coefficient and residual water saturation factor have been studied. The article presents the limits of changes and the average values of reservoir properties of rocks, and their comparison. On the basis of capillarimetric research, an evaluation of the structure of the void space of rocks was made.Conclusions. The correlation analysis has allowed establishing a series of empirical relationships between the reservoir parameters (density, effective porosity factor and residual water saturation factor) and, also, determining correlation dependences between porosity coefficients measured in atmospheric and reservoir conditions. There are their comparison characteristics. These relationships can be used in the data interpretation of geophysical studies of wells and in the modeling of porosity and permeability properties of consolidated rocks.
Keywords: siltstones; sandstones; reservoir properties; density; porosity coefficient; permeability coefficient; residual water saturation factor; correlation relationships